An audit of the multidisciplinary management of malignant bowel obstruction on an oncology ward in an acute tertiary hospital. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Ryan, Richella; Bruce, Emma; Leithead, Jane
Abstract : Background: Malignant bowel obstruction is common in advanced cancer. It is frequently associated with a poor prognosis. Management is complex and requires multidisciplinary input. Though management decisions need to be individualised, the assessment process leading to such decisions should be systematic. Aims: The primary aim was to provide baseline information on key areas of malignant bowel obstruction management for future auditing purposes. A secondary aim was to assess compliance with the current hospital guidelines for the medical management of this condition. Methods: The medical notes for 32 admissions to the oncology ward of an acute tertiary hospital between 31 July 2009 and 1 August 2010 were reviewed. Data was entered onto a proforma. Descriptive statistical analysis was performed using SPSS. Results: The majority of patients had advanced cancer with peritoneal metastases (28.88%). Ovarian was the most common primary site (17.57%). 15 (47%) patients were committed to a course of chemotherapy at presentation. The majority of patients had symptoms of nausea (26.81%), vomiting (26.81%), abdominal pain (26.81%) and altered bowel habit (27.78%). Medications were administered via a continuous subcutaneous infusion in 19 (60%) cases. A nasogastric tube was inserted in 10 (31%) cases. Cyclizine was the most commonly used first-line antiemetic (57%). Octreotide was rarely used (3.9%). Treatment of persisting bowel obstruction included: chemotherapy (13.41%), surgery (3.9.4%), radiotherapy (1.3%), stenting (5.15%) and venting gastrostomy (1.3%). 7 (22%) patients were commenced on parenteral nutrition. Twenty-seven patients (84%) survived to discharge and, of these, 20 (74%) were discharged home. Conclusion: The results indicate that the presentation and nature of malignant bowel obstruction is heterogeneous and that treatment decisions vary widely. The current local guidelines are under review to promote more consistent management and to guide referral to important disciplines.